Unmet treatment needs of gastroesophageal reflux disease in Asia: Gastroesophageal reflux disease in Asia Pacific Survey. Issue 12 (18th November 2014) - Goh, Khean Lee; Choi, Myung Gyu; Hsu, William Ping I; Chun, Hoon Jai; Mahachai, Varocha; Kachintorn, Udom; Leelakusolvong, Somchai; Kim, Nayoung; Rani, Abdul Aziz; Wong, Benjamin CY; Wu, Justin; Chiu, Cheng Tang; et al.
Abstract Background and Aim Data on patient satisfaction with proton pump inhibitor (PPI) therapy for gastroesophageal reflux disease (GERD) are scarce in Asia. The perspectives of Asian patients with GERD and their satisfaction with PPI therapy were investigated. Methods The GERD in Asia Pacific Survey (GAPS) was conducted from December 2011 to March 2012. Patients aged 21–55 years with self‐reported doctor‐diagnosed GERD, who had experienced symptoms in the previous 12 months, and were currently taking PPIs were enrolled. After a pilot study, a questionnaire was completed by respondents from six Asian countries during face‐to‐face interviews. Results A total of 450 patients with GERD participated in the GAPS. Although the respondents generally complied with treatment, response to therapy was only partially successful. Most respondents indicated that PPIs eliminated pain (72%), took effect within 30 min (76%), provided sustained relief (73%), and provided nocturnal relief (77%). However, 45% of respondents reported limited improvement in nocturnal symptoms, and 49% continued to take adjunctive therapy to manage their symptoms. After treatment, respondent's "well‐being" had improved. However, GERD still had a negative impact on well‐being for 76% of respondents after treatment, compared with 94% before treatment. Conclusions Asian patients reported a negative impact of GERD on their daily lives. Many respondents continued to experience symptoms despite reporting good compliance with PPI therapy, emphasizing the shortcomings of currently available therapy for GERD. This survey is the first to highlight Asian patients' perspectives of GERD and PPI therapy, and provides a platform for further evaluation.